(untitled) - FAO (Rome, 1999)
In this book specifications of certain food additives provide information on their identity and purity. The three main objectives of these specifications are to identify the substance that has been subjected to biological testing, to ensure that the substance is of the quality required for sale use in food and to reflect and encourage good manufacturing practice (GMP).
Keywords: food industry and trade,food supply